KEWAJIBAN NEGARA INDONESIA TERHADAP PERJANJIAN INTERNASIONAL YANG TELAH DIRATIFIKASI (Convention on The Protection of The Rights of All Migrant Workers of Their Families) - Elfia Farida (Administrative Law and Governance Journal, 2020)
International agreements have advantages over other sources of international law. International agreements are used consistently as a tool for cooperation or peaceful relations between countries regardless of their political, economic and social systems. Indonesia has also taken many binding actions on international treaties. If Indonesia is bound by an international agreement, then it is obliged not to carry out something that is contrary to the essence, purpose and purpose of the international agreement and morally must obey obligations arising from the existence of the international agreement in good faith (pacta sunt servanda). The International Convention on The Protection of the Rights of All Migrant Workers of Their Families has been ratified through Law No. 6 of 2012 so that Indonesia is obliged to realize the rights set out in the Convention into law in force in Indonesia, as a form of State protection for Indonesian migrant workers and members of their families. Keywords: state obligations, international treaties, ratification Abstrak Perjanjian internasional mempunyai kelebihan dibandingkan sumber hukum internasional lainnya. Perjanjian internasional digunakan secara konsisten sebagai alat kerja sama atau hubungan damai antar negara apapun sistem politik, ekonomi dan sosialnya. Indonesia juga telah banyak melakukan tindakan pengikatan terhadap perjanjian internasional. Apabila Indonesia sudah terikat pada suatu perjanjian internasional, maka berkewajiban untuk tidak melaksanakan sesuatu yang bertentangan dengan esensi, maksud dan tujuan perjanjian internasional dan secara moral harus mentaati kewajiban-kewajiban yang timbul akibat adanya perjanjian internasional tersebut dengan iktikad baik (pacta sunt servanda).  International Convention on The Protection of The Rights of All Migrant Workers of Their Families  telah diratifikasi melalui UU No. 6 Tahun 2012 sehingga Indonesia berkewajiban merealisasikan hak-hak yang diatur dalam Konvensi ke dalam hukum yang berlaku di Indonesia, sebagai wujud pelindungan Negara kepada pekerja migran Indonesia dan anggota keluarganya. Kata Kunci:  kewajiban negara, perjanjian internasional, ratifikasi